Green Cities : Cities and Climate Change in Brazil - World Bank (Washington, DC, 2013)
Urban sources of greenhouse gas (GHG) emissions in Brazilian cities are growing. At the national level, the dominance of greenhouse gas emissions from deforestation in Brazil masks the fact that emissions from other sectors, like Energy, Transport and Waste, are growing quite rapidly in cities. Compared to other cities around the world, Brazilian cities have low per capita GHG emissions because of the high level of renewable energy production; but as Brazilian cities continue to grow, the pressure towards higher emissions will persist. The majority of emissions from Energy in Brazil result from the use of fossil fuels and electric power by industry. Industrial processes using fossil fuels will continue to be the largest contributor to emissions growth over the long-term, but electricity generation will produce the highest emissions increase in the period up to 2030. For the past three decades, the trend has been for industries to move away from city centers to peripheral locations that are cheaper and have easier access to distribution networks. However, all the GHG emissions inventories completed to date by Brazilian cities are limited to municipal boundaries, making it difficult to assess the role of industrial emissions at the metropolitan level. One clear trend within city boundaries is that residential consumption of electricity is increasing. As households become wealthier, the size of housing units tend to get larger and the number of domestic appliances increase and residential consumption of electricity is expected to grow drastically in the next two decades.Transport emissions are rapidly growing, especially in urban areas. Fossil fuel based emissions in Brazil are low compared to other countries due to the prominence of renewable-energy sources for electricity and fuels. In fact, ethanol substitutes for two-fifths of gasoline fuel. However, transport-sector emissions are rapidly growing due to increased motorization and congestion. This is coupled with a tendency for smaller agglomerations to grow in a sprawling manner, which is directly impacting the growth of GHG emissions, since the amount of vehicle travel is linked to urban form, i.e. the location of housing, jobs, commerce and entertainment.A distinguishing characteristic of Brazilian cities is the high percentage of emissions from waste. The waste sector constitutes about 4 percent of GHG emissions on average in cities.1 A key driver of waste emissions is the amount of waste produced and collected. In Brazil the amount of waste collected has increased by about 4 percent per year since 1970. The amount of solid waste collected in urban areas is expected to continue increasing in the next two decades due to increased generation of waste and improvements in the collection system. This will likely result in an even higher share of GHG emissions for the overall sector.Climate change impacts are widespread. Climate impacts from global warming in major Brazilian cities have been identified and include flooding from intense storms, increased temperatures, and droughts. Sea level rise is also identified as a concern for Brazil because 25 percent of Brazil s population lives in coastal cities. Brazilian cities are taking action against climate change. In response to concerns about global climate change, Brazilian cities have been world leaders in defining GHG emissions reduction targets and adopted local climate change laws. Some cities have completed GHG inventories, established reduction targets, and taken measures to mitigate emissions.